Portfolio Assessment Strategies to Improve Prospective Teacher Competency in Islamic Religious Education Learning - Hidayah, Anis Rofi; Hanifiyah, Fitriyatul; Fauzi, Ahmad (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2025)
One of the most critical competencies a teacher must possess is effectively assessing learning. To achieve this, prospective teachers need to develop the skill of crafting high-quality questions that meet three essential criteria: alignment with learning objectives, the capacity to measure higher-order cognitive skills, and the use of precise and clear question narratives. This study focuses on implementing portfolio assessment in the Islamic Religious Education (PAI) learning evaluation course, which aims to improve students' ability to make questions as a tool in learning evaluation. The research adopts a qualitative approach, specifically Classroom Action Research (CAR), to explore the impact of this intervention. The findings of this study reveal significant improvements in students' ability to formulate questions, as measured by three key indicators. First, students demonstrated a marked progression in their ability to create questions that align with learning objectives, advancing from the